Peran Artifical Inteligence (AI) Dalam Meningkatkan Literasi Digital Dan Kemampuan Berpikir Kritis Mahasiswa - Ernalia, Urfa; Alayda Zahra, Fifi; Alexander Alim, Jesi; Dwi Anggriani, Mitha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the role of Artificial Intelligence (AI) in improving digital literacy and critical thinking skills among students in the era of Society 5.0. The presence of AI integrated with digital technology brings both opportunities and challenges in the learning process. This study uses a quantitative approach with a survey method involving 30 students selected through purposive sampling. The research instrument was a questionnaire with a five-point Likert scale, covering two main indicators, namely digital literacy and critical thinking skills. The data were analyzed descriptively through percentages, frequencies, and mean values. The results showed that the highest aspect of digital literacy was in the ethics of communication in the digital space (21.45%), while the lowest aspect was in active participation in the digital space (18.92%). In the critical thinking indicator, the highest achievement was in the ability to make estimates and integrate (20.89%), while the lowest was in the ability to draw conclusions (19.55%). These findings confirm that the use of AI contributes significantly to improving students' technical, ethical, and analytical skills. However, strengthening digital literacy and the wise use of AI is necessary so that students do not merely become passive consumers but active, critical, and creative producers of knowledge. Thus, AI can become an important catalyst in building an innovative, ethical learning ecosystem. However, it is necessary to strengthen digital literacy and the wise use of AI so that students do not merely become passive consumers, but active, critical, and creative producers of knowledge. Thus, AI can be an important catalyst in building an innovative, ethical, and sustainable learning ecosystem in higher education.